THE NEXUS BETWEEN FDI NET INFLOWS AND DOING BUSINESS INDEX: ANALYSIS FROM UZBEKISTAN (Scientific journal of the Fergana State University, 2024)
This paper investigates the relationship between Foreign Direct Investment (FDI) net inflows and the Doing Business Index (DBI) across a diverse sample of countries. FDI plays a crucial role in fostering economic development and global integration, while the DBI serves as a comprehensive measure of the regulatory environment for businesses. Using econometric techniques and panel data analysis, we examine the extent to which improvements in the ease of doing business influence FDI inflows. Our findings reveal a significant positive relationship between FDI net inflows and DBI scores, indicating that countries with higher DBI scores tend to attract greater foreign investment. This suggests that policies aimed at enhancing the business environment and reducing regulatory barriers can effectively attract FDI and stimulate economic growth. The insights from our study have important implications for policymakers, investors, and researchers interested in understanding the determinants of FDI inflows and promoting sustainable economic development.